2016
DOI: 10.1016/j.buildenv.2015.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of changes of indoor air pressure and air exchange rate in vapor intrusion scenarios

Abstract: There has, in recent years, been increasing interest in understanding the transport processes of relevance in vapor intrusion of volatile organic compounds (VOCs) into buildings on contaminated sites. These studies have included fate and transport modeling. Most such models have simplified the prediction of indoor air contaminant vapor concentrations by employing a steady state assumption, which often results in difficulties in reconciling these results with field measurements. This paper focuses on two major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…This pressure gradient around building influences the pressure difference between indoor and outdoor, which is an important feature that was not previously identified by VI models. 18, 20 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This pressure gradient around building influences the pressure difference between indoor and outdoor, which is an important feature that was not previously identified by VI models. 18, 20 …”
Section: Resultsmentioning
confidence: 99%
“…Song et al 19 assessed the influence of stack and wind effects on soil gas entry rate and outdoor air flowrate through the building, however the authors did not consider wind effect (or wind direction) on subsurface pressure, which influences on soil gas entry rate. 19 Shen and Suuberg 18 showed that the AER and indoor air pressure variation can result in substantial variation in indoor air contaminant concentration; however they did not indicate how wind and temperature influence AER or indoor air pressure. 18 Although these studies are important in highlighting the importance of aboveground processes on VI, these studies have not considered how AER and indoor air pressure are directly connected to wind and stack effects, and how together all of these parameters collectively alter VI exposure risks.…”
Section: Theory and Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Governing Equations. A 2D numerical model is built to investigate the influence of groundwater table fluctuations on vapor intrusion using a finite element code COMSOL Multiphysics, which has been widely adopted in previous studies to solve the problem of vapor transport from the contaminant source to the dwelling through the building foundation crack (e.g., [30][31][32][33]). The development and use of this code to solve typical vapor intrusion problems have been described in detail in Pennell et al [30].…”
Section: Numerical Modelingmentioning
confidence: 99%
“…Diallo et al (2015) presented some semiempirical models to quantity the entry of VOCs into buildings as a function of a series of site-specific parameters such as soil diffusion coefficients, diffusion coefficients of the slab, source depth, and indoor ventilation rate. Shen and Suuberg (2016) used a 3D finite element model to examine the influence of indoor air pressure and air exchange rate on indoor air contaminant vapor concentrations showing how these parameters can influence the temporal indoor air contaminant vapor concentration changes. Yao et al (2020a) used a 3D numerical model to evaluate the impact of a building's indoor pressure fluctuations in the presence of an impervious pavement surrounding the building.…”
Section: Entry Into the Buildingmentioning
confidence: 99%